THE VALUE OF PROFESSIONAL QUALITIES IN THE TARGET MODEL OF THE EDUCATIONAL PROCESS OF MILITARY TRAINING (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article deals with a problem of professional training of future military personnel. The author shows the necessity of developing professional knowledge, skills and abilities, as well as courage, ability to fulfill orders, discipline, self-control and dedication, which are regarded as an obligatory component of the professional training in higher military educational institutions. The effectiveness of professional activities of military personnel is determined by a system of socio-psychological, technical, medical and biological, as well as special military skills.
Keywords: Professional qualities, professional training of military personnel, military education.